Comparative Analysis of Mannans Extraction Processes from Spent Yeast Saccharomyces cerevisiae - Margarida Faustino; Joana Durão; Carla F. Pereira; Ana Sofia Oliveira; Joana Odila Pereira; Ana M. Pereira; Carlos Ferreira; Manuela E. Pintado; Ana P. Carvalho (Foods, 2022)
Mannans are outstanding polysaccharides that have gained exponential interest over the years. These polysaccharides may be extracted from the cell wall of Saccharomyces cerevisiae, and recovered from the brewing or synthetic biology industries, among others. In this work, several extraction processes—physical, chemical and enzymatic—were studied, all aiming to obtain mannans from spent yeast S. cerevisiae. Their performance was evaluated in terms of yield, mannose content and cost. The resultant extracts were characterized in terms of their structure (FT-IR, PXRD and SEM), physicochemical properties (color, molecular weight distribution, sugars, protein, ash and water content) and thermal stability (DSC). The biological properties were assessed through the screening of prebiotic activity in Lactobacillus plantarum and Bifidobacterium animalis. The highest yield (58.82%) was achieved by using an alkaline thermal process, though the correspondent mannose content was low. The extract obtained by autolysis followed by a hydrothermal step resulted in the highest mannose content (59.19%). On the other hand, the extract obtained through the enzymatic hydrolysis displayed the highest prebiotic activity. This comparative study is expected to lay the scientific foundation for the obtention of well-characterized mannans from yeast, which will pave the way for their application in various fields.